Comparison of Corruption Eradication Institutions in Various Countries (Indonesia, Hong Kong, Japan, Australia, New Zealand) - Setiawan, Agung; Ashari, Ashari; Fallahiyan, Muh. Alfian; Kafrawi, Rachman Maulana (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This study discusses the Corruption Eradication Commission (KPK) since 2019 there has been a significant change, because the second amendment to the KPK Law has been ratified through Law Number 19 of 2019, Indonesia's ranking index is at 115, amputated authority and declining performance. The study conducted a comparative approach between the Indonesian KPK and the corruption eradication institutions of Hong Kong, Japan, Australia and New Zealand. It was found that Asian and Australian countries have less authority, but are ranked high (3 to 14) in eradicating corruption compared to Indonesia which is ranked 115. The results of the study show that there has been a change in the position of the KPK institution in terms of state administration which is no longer an Auxiliary body but a state organ, full authority but requires permission from the supervisory board, accountability and full control by the government (executive).